The Mexican Oil Boom: 1977-1985 - Michael Gavin (Inter-American Development Bank, Office of the Chief Economist, 1996)
The Mexican oil boom was characterized by a period of high investment, followed by capital flight. The private sector and households responded to the 1977-1981 windfall by attaining high savings rates. On the other hand, the Mexican government, the proprietor of the state oil company and the principal beneficiary of the oil boom, used windfall revenues to finance unsustainable spending and even engage in dissaving. These policies produced macroeconomic dislocations that made Mexico highly vulnerable to the inevitable external shocks.
Keywords: 330